Improving Person-Centered Care Through Effective Design - Zeisel, John (Generations (San Francisco, Calif.), 2013)
This article presents eight design criteria-primarily but not exclusively for residential settings-that support the personhood of people living with dementia by providing them with greater understanding and control over their physical environment. The article describes how each criterion, based in a neuroscience understanding of hard-wired brain function, leads to a greater sense of self, improved relationships among individuals, staff, and family members, and ultimately person-centered care.